Communicating Climate Change : A Guide for Educators - Armstrong, Anne K.; Schuldt, Jonathon P.; Krasny, Marianne E. (Book collections on Project MUSE., 2018)
"This book provides environmental educators with an understanding of how their audiences engage with climate change information as well as with concrete, empirically tested communication tools they can use to enhance their climate change program"--